The early Muslim conquest of Syria : an English translation of al-Azdī's Futūḥ al-Shām /: an English translation of al-Azdī's Futūḥ al-Shām. (2019) - Azdī, Muḥammad ibn ʿAbd Allāh, approximately 781
No abstract available